Design of a Web-Based Mail Management System at The Sub- District Office of Tano Tombangan Angkola - Ichsan, Aulia (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2022)
In the process of modernizing the administration, it is necessary to implement an information system that can support all administrative activities in an institution, institution or company. At the CAMAT Tano Tombangan Angkola office, South Tapanuli Regency, there is still a conventional letter archive management method where archive recording is still carried out using books and stationery. This often causes many problems, such as loss of documents, damage or documents that are not recorded. During the practical work, the author tries to develop an application that can record all archives in the agency. Then it will be stored in a database and can be accessed anytime and anywhere. As a result, many benefits are provided to the agency, such as more structured and neat archive data collection.